2021
DOI: 10.3892/etm.2021.10329
|View full text |Cite
|
Sign up to set email alerts
|

BMP‑2 alleviates heart failure with type 2 diabetes mellitus and doxorubicin‑induced AC16 cell injury by inhibiting NLRP3 inflammasome‑mediated pyroptosis

Abstract: Chronic heart failure (CHF) and diabetes mellitus are associated with morbidity and mortality. CHF and diabetes generally simultaneously occur, resulting in adverse outcomes. Diabetes complicates cardiomyopathy and exacerbates heart failure conditions. An increase in natriuretic peptides, including atrial natriuretic peptide (ANP), and another endsogenously generated peptide, brain natriuretic peptide (BNP), serves an essential role in CHF. The aim of this study was to explore the molecular regulation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…It has been reported that the BMP pathway is enriched for HFpEF but not HFrEF ( 26 ). BMP2 has been found to alleviate heart failure with type 2 diabetes by inhibiting inflammasome formation ( 27 ), and is inversely correlated with the concentrations of atrial natriuretic peptide and brain natriuretic peptide in chronic heart failure patients with diabetes. Another study observed increased BMP6 in chronic heart failure patients, suggesting that BMP6 may be involved in the pathophysiology of systolic heart failure ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the BMP pathway is enriched for HFpEF but not HFrEF ( 26 ). BMP2 has been found to alleviate heart failure with type 2 diabetes by inhibiting inflammasome formation ( 27 ), and is inversely correlated with the concentrations of atrial natriuretic peptide and brain natriuretic peptide in chronic heart failure patients with diabetes. Another study observed increased BMP6 in chronic heart failure patients, suggesting that BMP6 may be involved in the pathophysiology of systolic heart failure ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the tight correlation between chemotherapy-induced tissue damage and pyroptosis also provides a promising strategy to reduce toxicity by inhibition of pyroptosis. For instance, DOX, a common antineoplastic agent, can cause cardiotoxicity via pyroptosis in clinical practice [ 193 195 ]. MCC950, an NLRP3 inflammasome inhibitor, could obviously suppress myocardial inflammation and fibrosis by inhibiting pyroptosis of cardiomyocyte in DOX-treated mice [ 193 ].…”
Section: Overview Of Pyroptosismentioning
confidence: 99%
“…NOD‐like receptor protein 3 (NLRP3) inflammasome is a key factor of pyroptosis, and after activation, NLRP3 interacts with apoptosis‐associated speck‐like protein (ASC), recruits and cleaves pro‐caspase‐1, thus activating caspase‐1, which cleaves gasdermin D(GSDMD) with producing GSDMD‐N, and further triggers the pyroptotic cascade (activated caspase‐1 induces inflammation by cleaving pre‐interleukin [IL]‐1β and pre‐IL‐18 into IL‐1β and IL‐18, which are biomarkers of pyroptotic) 5 . In recent years, studies confirmed that NLRP3 inflammasome is activated during several cardiac disorders, and NLRP3 inflammasome‐mediated pyroptosis aggravates pressure overload‐induced cardiac hypertrophy, fibrosis, dysfunction, 6 which is a key pathological factor underlying HF 7–9 …”
Section: Introductionmentioning
confidence: 99%
“…5 In recent years, studies confirmed that NLRP3 inflammasome is activated during several cardiac disorders, and NLRP3 inflammasome-mediated pyroptosis aggravates pressure overload-induced cardiac hypertrophy, fibrosis, dysfunction, 6 which is a key pathological factor underlying HF. [7][8][9] ROS acts as a major trigger of NLRP3 inflammasome activation, 10 NADPH oxidase, mainly subunit NOX2 and NOX4, is the main source of intracellular ROS, and the expression of NADPH is up-regulated in HF. 11,12 ER is essential for protein synthesis, protein folding, protein translocation and calcium homoeostasis.…”
mentioning
confidence: 99%